2014
DOI: 10.1590/s0102-86502014001800003
|View full text |Cite
|
Sign up to set email alerts
|

Presentation of an experimental method to induce in vitro ("organ chambers") respiratory acidosis and its effect on vascular reactivity

Abstract: PURPOSE:To create in vitro a model to generate acidosis by CO 2 bubbling "organ chambers", which would be useful for researchers that aim to study the effects of acid-base disturbs on the endothelium-dependent vascular reactivity. METHODS:Eighteen male Wistar rats (230-280g) were housed, before the experiments, under standard laboratory conditions (12h light/ dark cycle at 21°C), with free access to food and water. The protocol for promoting in vitro respiratory acidosis was carried out by bubbling increased c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…Another study from our research group aimed to study the in vitro vascular responses induced by hypercapnic extracellular acidification (AH), as well as the endothelium-dependent mechanisms that are involved in the responses. It has been concluded that: 1) AH causes endothelium-dependent relaxation; 2) Indomethacin failed to block this relaxation, but the limitation of the method does not allow discarding some prostanoid paper; 3) Relaxation of the HA vessel is mediated via cGMP/NO and; 4) Hyperpolarization occurs by the action of the potassium channels SKCa, KATP, and Kv, without depending on BKCa channels (Nadai et al, 2014).…”
Section: (With 2 Figures)mentioning
confidence: 99%
“…Another study from our research group aimed to study the in vitro vascular responses induced by hypercapnic extracellular acidification (AH), as well as the endothelium-dependent mechanisms that are involved in the responses. It has been concluded that: 1) AH causes endothelium-dependent relaxation; 2) Indomethacin failed to block this relaxation, but the limitation of the method does not allow discarding some prostanoid paper; 3) Relaxation of the HA vessel is mediated via cGMP/NO and; 4) Hyperpolarization occurs by the action of the potassium channels SKCa, KATP, and Kv, without depending on BKCa channels (Nadai et al, 2014).…”
Section: (With 2 Figures)mentioning
confidence: 99%
“…Esses estudos adotaram modelo experimental in vivo e in vitro de distúrbios metabólicos e respiratórios e, os resultados tem permitido uma melhor compreensão sobre a influência do pH sobre a função vascular: 1) a acidificação extracelular induzida com HCl em aorta torácica de rato causou relaxamento dependente do pH nos anéis com endotélio intacto e anéis aórticos sem endotélio pré-contraídos com Phe; 2) a acidose metabólica in vitro induzida por borbulhamento de concentações aumentadas de CO 2 possibilitou o registro de forças isométricas; 3) a acidose metabólica aguda, in vivo, potencializa a resposta vasodilatadora da ACh e promove aumento nos níveis de NO. (Celotto et al 2011;Nadai et al 2014;Celotto et al 2016).…”
Section: Lista De Abreviaturas Siglas E Símbolosunclassified